Mathematical Communication Process Profile of Prospective Mathematics Teachers Based on Self-Confidence - Darto; Kartono; Widowati; Mulyono (Instructional Development Journal, 2026)
Self-confidence is one of the affective aspects that can support mathematical communication skills. The research focuses on explaining students' mathematical communication processes in solving problems regarding self-confidence. The approach used is qualitative. The research instrument consists of questionnaires, tests, and interviews. The results of the self-confidence questionnaire were categorized into high, medium, and low. Each category took one person as a respondent. Data analysis uses the reduction stage, displaying results and conclusions. The research results are a mathematical communication process based on self-confidence, including identification, representation, algorithms, and evaluation. Students in the high and medium self-confidence categories show characteristics of good communication processes, namely identification, representation, algorithms, and evaluation. Students use symbols appropriately to explain known information and problems and write detailed answers. Students in the low self-confidence category need help translating mathematical information and symbols. This results in the algorithm stage needing to get the right results. This condition shows that the identification and representation stages are critical initial processes in mathematical communication